Anticipating Xenogenic Pollution at the Source: Impact of Sterilizations on DNA Release From Microbial Cultures - Calderón-Franco, David; Lin, Qingnan; van Loosdrecht, Mark C. M.; Abbas, Ben; Weissbrodt, David G. (Frontiers in Bioengineering and Biotechnology, 2020)
The dissemination of DNA and xenogenic elements across waterways is under scientific and public spotlight due to new gene-editing tools, such as do-it-yourself (DIY) CRISPR-Cas kits deployable at kitchen table. Over decades, prevention of spread of genetically modified organisms (GMOs), antimicrobial resistances (AMR), and pathogens from transgenic systems has focused on microbial inactivation. However, sterilization methods have not been assessed for DNA release and integrity. Here, we investigated the fate of intracellular DNA from cultures of model prokaryotic (Escherichia coli) and eukaryotic (Saccharomyces cerevisiae) cells that are traditionally used as microbial chassis for genetic modifications. DNA release was tracked during exposure of these cultures to conventional sterilization methods. Autoclaving, disinfection with glutaraldehyde, and microwaving are used to inactivate broths, healthcare equipment, and GMOs produced at kitchen table. DNA fragmentation and PCR-ability were measured on top of cell viability and morphology. Impact of these methods on DNA integrity was verified on a template of free λ DNA. Intense regular autoclaving (121°C, 20 min) resulted in the most severe DNA degradation and lowest household gene amplification capacity: 1.28 ± 0.11, 2.08 ± 0.03, and 4.96 ± 0.28 logs differences to the non-treated controls were measured from E. coli, S. cerevisiae, and λ DNA, respectively. Microwaving exerted strong DNA fragmentation after 100 s of exposure when free λ DNA was in solution (3.23 ± 0.06 logs difference) but a minor effect was observed when DNA was released from E. coli and S. cerevisiae (0.24 ± 0.14 and 1.32 ± 0.02 logs differences with the control, respectively). Glutaraldehyde prevented DNA leakage by preserving cell structures, while DNA integrity was not altered. The results show that current sterilization methods are effective on microorganism inactivation but do not safeguard an aqueous residue exempt of biologically reusable xenogenic material, being regular autoclaving the most severe DNA-affecting method. Reappraisal of sterilization methods is required along with risk assessment on the emission of DNA fragments in urban systems and nature.